Long-Term Effects of Environmental Lead Exposure on Blood Pressure and Plasma Soluble Cell Adhesion Molecules in Young Adults: A Follow-Up Study of a Prospective Cohort in Kosovo. (8th January 2018) - Camaj, Pashko R.; Graziano, Joseph H.; Preteni, Emine; Popovac, Dusan; LoIacono, Nancy; Balac, Olgica; Factor-Litvak, Pam
Abstract : Background and Aims . Epidemiologic studies examining the relationship between environmental lead (Pb) exposure and blood pressure (BP) generally report small associations between blood lead concentration (BPb) and BP. However, these studies are predominantly cross-sectional. In addition, no epidemiologic studies evaluate associations between either current or past Pb exposure and serum levels of markers of systemic inflammation and endothelial dysfunction, including soluble vascular adhesion molecule (sVCAM-1) and soluble intercellular cell adhesion molecule (sICAM-1). We prospectively investigate these associations later in life . Methods . From our original prospective birth cohort study in Mitrovica (a mining town) and Prishtina (a control town), Kosovo, from 1985 to 1998, we located and assessed BPb and BP in 101 participants (mean age of 24.9 years old) in 2011. Results . We found highly statistically significant association between concurrent BPb and sVCAM-1 in men and a marginally significant association between concurrent PBb and sICAM.-1 in women. We did not find evidence of mediation. Conclusion . Current study results, along with previously reported findings on this cohort, provide evidence for the hypothesis that exposure to Pb leads to small increases in sBP and perhaps to increased circulating levels of sVCAM-1 and sICAM-1 later in life.